SKRINING DIABETES MELLITUS DI KOMUNITAS YOGA DHSP BALI, BANJAR SINGIN, SELEMADEG, KABUPATEN TABANAN - Agung Setiabudi,; Putu Setiani,; Anak Agung Sagung Candra Mahesuari,; Ni Ketut Lyra Sakhya Melani,; Ida Ayu Puspa Juwita Manuaba, (J-ABDI: Jurnal Pengabdian kepada Masyarakat, 2025)
Diabetes mellitus (DM) is a global health problem with increasing prevalence, including in Indonesia. Community-based screening is an important strategy for detecting cases early, reducing complications, and reducing the burden of health costs. The results show that community screening is effective in increasing the detection rate of new cases and facilitating early intervention. DM screening in the DHSP Bali yoga community was obtained as many as 12.5% had diabetes mellitus. Further treatment requires the active role of first-level health facilities. Further implementation of the program requires policy support, community involvement, and trained health workers to achieve sustainable diabetes control goals.